Matrix derivation of the Fibonacci series (you can give up the matrix if you cannot understand it) and the Fibonacci Matrix
I. Matrix Multiplication
Set the matrix A and B to meet the following requirements: the number of columns of A = the number of rows of B
Calculation rules for matrix multiplication:
Multiply each row of matrix A by each column of matrix B.
*
=
=
Ii. Matrix derivation of the Fibonacci series
First, we want
Fib [I] = Fib [I-1] + Fib [I-2];
So the I of the Fibonacci series is related to two numbers, Fib [I-1] + Fib [I-2 ].
Then we can set the first matrix.
M1 =
Because we need to use the Matrix to launch the nth entry of Fibonacci.
So we set the next item of M1 to M3.
Then M3 = (that is, let the subscript of M1 move one bit after the whole)
Now we need a Transitional Matrix M2 to implement this operation from M1 to M3.
Because M1 is a 1*2 matrix
M3 is also a 1*2 matrix
So M2 must be a 2*2 matrix.
(Cause: 1. the M1 column must be the same as the M2 row.
2. The number of M3 columns is 2)
Set M2 =
So
A * fi-2 + B * fi-1 = fi-1
C * fi-2 + d * fi-1 = fi ②
This statement does not seem to be available.
But let's think about it.
When a = 0 & B = 1
When c = 1 & d = 1 (Fib [I] = Fib [I-1] + Fib [I-2])
Therefore, we can easily obtain the M2 matrix.
M2 =
3. A simple example
Set fi = fi-1 + 2fi-2 + 3fi-3
Obtain M1, M2, and M3 according to the above method.
Tip: matrix derivation without Coefficients
(We recommend that you first check the problem)
Solution:
Set M1 =
M3 =
Then M2 must be a 3*3 matrix.
Set M2 =
Then a * fi-1 + B * fi-2 + c * fi-3 = fi = fi-1 + 2fi-2 + 3fi-3
D * fi-1 + e * fi-2 + f * fi-3 = fi-1
G * fi-1 + h * fi-2 + I * fi-3 = fi-2
Easy to get a = 1, B = 2, c = 3
D = 1, e = 0, f = 0
G = 0, h = 0, I = 0
So
M2 =